DNA sequencing, anatomy, and calcification patterns support a monophyletic, subarctic, carbonate reef‐forming Clathromorphum (Hapalidiaceae, Corallinales, Rhodophyta). Issue 1 (20th January 2015) - Adey, Walter H.; Hernandez‐Kantun, Jazmin J.; Johnson, Gabriel; Gabrielson, Paul W.; Vis, M.
<x xml:space="preserve">Abstract</x> For the first time, morpho‐anatomical characters that were congruent with DNA sequence data were used to characterize several genera in Hapalidiaceae—the major eco‐engineers of Subarctic carbonate ecosystems. DNA sequencing of three genes (SSU, rbcL, ribulose‐1, 5‐bisphosphate carboxylase/oxygenase large subunit gene and psbA, photosystem II D1 protein gene), along with patterns of cell division, cell elongation, and calcification supported a monophyletic Clathromorphum. Two characters were diagnostic for this genus: (i) cell division, elongation, and primary calcification occurred only in intercalary meristematic cells and in a narrow vertical band (1–2 μm wide) resulting in a "meristem split" and (ii) a secondary calcification of interfilament crystals was also produced. Neopolyporolithon was resurrected for N. reclinatum, the generitype, and Clathromorphum loculosum was transferred to this genus. Like Clathromorphum, cell division, elongation, and calcification occurred only in intercalary meristematic cells, but in a wider vertical band (over 10–20 μm), and a "meristem split" was absent. Callilithophytum gen. nov. was proposed to accommodate Clathromorphum parcum, the obligate epiphyte of the northeast Pacific endemic geniculate coralline, Calliarthron. Diagnostic for this genus were epithallial cells terminating all cell filaments (no dorsi‐ventrality was present), and a distinct "foot" was embedded in the host. Leptophytum, based on its generitype, L. laeve, was shown to be a distinct genus more closely related to Clathromorphum than to Phymatolithon. All names of treated species were applied unequivocally by linking partial rbcL sequences from holotype, isotype, or epitype specimens with field‐collected material. Variation in rbcL and psbA sequences suggested that multiple species may be passing under each currently recognized species of Clathromorphum and Neopolyporolithon.